A Level Set Approach for a Premixed Flame Based on a New Concept of Flame Speed - Yingjie LIU; Nobuyuki OSHIMA (Journal of Thermal Science and Technology, 2011)
In this paper we propose a new level set approach to describe not only a flame's surface but also to the flame's spatial distribution. First, we derived the mathematical formulation for a one-dimensional laminar premixed flame, where the steady flame has a finite thickness depending on the diffusion flux whose physical quantity such as temperature has a relation to index function G . Further, to investigate the relationship between the present model and Inage's model, we extracted the physical meaning from the energy equation. We also validated another important parameter, the heat reaction release rate using the modified G-equation. The analysis of the heat release term leads to the definition of local flame speed, describing the distribution in the flame thickness. We evaluated the distribution of local flame speed with scalar G based on the one-dimensional solutions of premixed flames obtained by the detailed chemical reaction GRI-Mech3.0 using CHEMKIN. For CH4/Air premixed fuel, we carried out a series of calculations with different fuel rates and inlet temperatures. Based on the linear distribution of local flame speed, the modified G-equation can again be certified as the hyperbolic tangent profile.